1992
DOI: 10.1037/0278-7393.18.4.703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contextual features on the activation of ambiguous word meanings.

Abstract: Three studies examined whether initial meaning activation is sensitive to context. Experiment 1 demonstrated that contextually appropriate targets were activated more than inappropriate targets. Experiment 2 evaluated activation across intervals of 0, 300, and 600 ms. Constraining sentences activated contextually appropriate meanings over inappropriate meanings. This was maintained across the intervals for highly salient targets. Less-salient targets, although initially activated, were no longer activated 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 34 publications
(50 reference statements)
5
80
2
1
Order By: Relevance
“…However, the results are also consistent with a context-sensitive approach, in which context guides but does not necessarily determine meaning access (Paul, Kellas, Martin, & Clark, 1992). Both ofthese approaches can account for the present results if we assume that meaning frequency acts as a default for activation level, and context effects are a function ofthe basic activation due to frequency.…”
Section: Discussionsupporting
confidence: 78%
“…However, the results are also consistent with a context-sensitive approach, in which context guides but does not necessarily determine meaning access (Paul, Kellas, Martin, & Clark, 1992). Both ofthese approaches can account for the present results if we assume that meaning frequency acts as a default for activation level, and context effects are a function ofthe basic activation due to frequency.…”
Section: Discussionsupporting
confidence: 78%
“…The finding that only the contextually appropriate meaning for an ambiguity is active immediately following its presentation in a sentence supports this selective position (Glucksberg et al, 1986;Paul et al, 1992;Simpson, 1981;Simpson & Krueger, 1991).…”
Section: Models Of Ambiguous Word Processingsupporting
confidence: 54%
“…The early seminal research of Swinney (1979) and Seidenberg, Tanenhaus, Leiman, and Bienkowski (1982) supported a language system that is modular in architecture (Fodor, 1983), in which the immediate activation of word meanings proceeds without influence from discourse context and general world knowledge. This early evidence was contradicted by later research (e.g., Paul, Kellas, Martin, & Clark, 1992;Simpson & Krueger, 1991;Van Petten & Kutas, 1987), which showed that context can have an immediate influence on ambiguity resolution, thus supporting an interactive-activation viewpoint (e.g., McClelland, 1987) in which discourse context and world knowledge can immediately influence the resolution of lexical ambiguity. More recent research has suggested that the resolution of lexical ambiguity depends on the factors of meaning frequency, type of context used, and context strength.…”
Section: Situation-based Knowledge and The Resolution Of Lexical Ambicontrasting
confidence: 38%
“…More recent research has suggested that the resolution of lexical ambiguity depends on the factors of meaning frequency, type of context used, and context strength. For example, Tabossi, Colombo,and Job (1987) and Paul et al (1992) have demonstrated that feature-denoting contexts could be used to prime probe words representing those features of ambiguous words. And in a series of studies, Rayner and colleagues (e.g., Dopkins, Morris, & Rayner, 1992;Duffy, Morris, & Rayner, 1988;Rayner, Pacht, & Duffy, 1994) have shown that an intricate relationship exists between meaning frequency and biasing context in lexical ambiguity resolution (see also Hogaboam & Perfetti, 1975).…”
Section: Situation-based Knowledge and The Resolution Of Lexical Ambimentioning
confidence: 99%